On the Uncertain Taxonomic Identity of Adenomera hylaedactyla (Cope, 1868) and the Composite Type Series of A. andreae (Müller, 1923) (Anura, Leptodactylidae) - De Carvalho, Thiago R. [UNESP]; Giaretta, Ariovaldo A.; Maciel, Natan M.; Barrera, Diego A.; Aguilar-Puntriano, César; Haddad, Célio F. B. [UNESP]; Kokubum, Marcelo N. C.; Menin, Marcelo; Angulo, Ariadne (American Society of Ichthyologists and Herpetologists (ASIH), 2019)
Adenomera andreae and A. hylaedactyla are two widespread Amazonian frogs that have been traditionally distinguished from each other by the use of different habitats, toe tip development, and more recently through advertisement calls. Yet, taxonomic identification of these species has always been challenging. Herein we undertake a review of type specimens and include new phenotypic (morphology and vocalization) and mitochondrial DNA information for an updated diagnosis of both species. Our morphological analysis indicates that the single type (holotype) of A. hylaedactyla could either belong to lineages associated with Amazonian forest-dwelling species (A. andreae clade) or to the open-formation morphotype (A. hylaedactyla clade). Given the holotype's poor preservation, leading to the ambiguous assignment of character states for toe tip development, as well as a vague type locality encompassing a vast area in eastern Ecuador and northern Peru, the identity of this specimen is uncertain. Morphology of toe tip fragments and the original species description suggest that A. hylaedactyla could correspond to at least two described species (A. andreae or A. simonstuarti) or additional unnamed genetic lineages of the A. andreae clade, all bearing toe tips expanded into discs. Analysis of morphometric data, however, clustered the holotype with the Amazonian open-formation morphotype (toe tips unexpanded). While additional data can be obtained from the holotype of A. hylaedactyla, at this time this type cannot be unequivocally assigned to any species of Adenomera distributed across eastern Ecuador and Peru's northernmost region of Loreto. For the time being, the name A. hylaedactyla still accommodates the only Amazonian open-habitat species. As to the type series of Adenomera andreae, a forest-associated species with toe tips fully expanded (developed into small discs) from eastern Brazilian Amazonia, we found that one of its paratypes shares a morphotype with the open-habitat species and is reassigned to A. hylaedactyla. With the taxonomic identity of A. hylaedactyla unresolved, formal descriptions of cryptic species complexes within the A. andreae clade distributed across the type locality of A. hylaedactyla run the risk of a possible future synonymization with A. hylaedactyla. Yet, not naming more circumscribed and potentially threatened cryptic species puts them at risk, as they would probably not qualify for conservation funding. Given the current fire crisis in the Amazon Basin, the risk of losing species before they are described far outweighs the risk of synonymization. We recommend that researchers prioritize descriptions based on the potential extinction risk of new species.